What is behind high turnover: a questionnaire survey of hospital nursing care workers in Shanghai, China - Yan Wang; Huiyun Yuan (BMC, 2018)
Abstract Background Currently, hospital nursing care workers (hereafter referred to as HNCWs) have become an important part of the healthcare system in China. They exist in nearly all of the public hospitals and in some private hospitals, making up 20 to 30% of the total nursing staff and providing 30 to 40% of basic nursing care for patients. However, many studies have shown that the turnover rate of HNCWs is very high, with average annual rates of 20 to 45%. We conducted this survey to explore their turnover intentions and related factors and present some suggestions to improve their retention rate. Methods A total of 514 HNCWs employed at 11 hospitals in Shanghai participated in this study. The inclusion criteria were as follows: (1) being a certified HNCW, (2) having worked as an HNCW for more than 1 year, and (3) volunteering to take part in the survey. Results The overall turnover intention of the HNCWs was 41.3%. Influencing factors include education (βeta = 0.201, P = 0.000), wages (βeta = − 0.920, P = 0.000), management satisfaction, (βeta = − 0.213, P = 0.000), satisfaction with wages (βeta = − 0.612, P = 0.000), satisfaction with working hours (βeta = − 0.270, P = 0.000), satisfaction with their own work (βeta = − 0.066, P = 0.027), work stress (βeta = 0.726, P = 0.000), enjoyment of the job (βeta = − 0.141, P = 0.000) and hours of sleep (βeta = − 0.046, P = 0.037). Conclusions Decreasing HNCWs' turnover intentions and the overall turnover rate is important for improving the quality of healthcare. More attention should be paid to this issue in the enactment of health policy.